Experimental Investigation and Reliability Analysis on Wear Performance of AA6061-B4C-Nanographite Hybrid Composites. (2018) - Gnanavelbabu, A.; Muthazhagan, C.; Rajkumar, K.; Ayyanar, S.; Loganathan, P.
Abstract: In the present investigation, the influence of B4 C on the mechanical, tribological behavior and reliability analysis of Al 6061 composites have been evaluated. Boron carbide and nanographite particles reinforced composites were produced through casting. The test results revel increase in hardness with increasing volume% (5-15) of ceramic particles. The hybrid composite with 10% volume fraction of B4 C and 15% volume fraction of NG exhibited the lowest wear rate at both speeds 0.7 m/s and 2.1 m/s with a constant sliding distance of 1000m. Response optimization indicates optimum levels for 30N of load, 2.1 m/s of speed, 10% of B4 C and 15% NG by the factors which contribute to the minimum wear. Contour plot is a diagrammatic representation of contributed optimized response from 8 to 12% of B4 C and 13 to 15% of NG. Reliability analysis on time to failure data on the mean life in sliding distance was 52739.155 km is found to be higher than the existing material.